Forest loss and fragmentation can promote the crowding effect in a forest-specialist primate - Gestich, Carla C.; Arroyo-Rodríguez, Víctor; Saranholi, Bruno H.; da Cunha, Rogério G. T.; Setz, Eleonore Z. F.; Ribeiro, Milton C. [UNESP] (Springer Nature, 2022)
Context: Forest loss and fragmentation are rapidly expanding across the tropics. Although forest loss is a major driver of the current biodiversity crisis, the effect of fragmentation remains debated, particularly for forest-specialist species. Objectives: We evaluated the univariate and combined effect of forest loss (percent of forest cover) and fragmentation (forest patch density) on populations of a forest-specialist primate, the black-fronted titi monkey (Callicebus nigrifrons), in the landscapes from a transitional zone between Atlantic Forest and Cerrado biomes. Methods: We surveyed titi monkey density in 14 landscapes. Using a multiscale and multimodel inference approach, we tested the relative effect of each landscape variable assessed at their respective scales of effect on titi monkey density. Results: Titi monkey density ranged from 0 to 12 groups/km2 and was best predicted by the combined effect of forest cover and patch density. Density increased in forest patches embedded in more deforested and fragmented landscapes. Interestingly, the effect of forest patch density was consistently positive along the entire evaluated forest cover gradient (9–42%). Conclusions: Our findings support that fragmentation per se can have positive effects on biodiversity, in this case, by increasing the likelihood that more individuals can be ‘rescued’ from deforestation and crowded in the remaining forest patches. Although the long-term consequences of living crowded in forest patches are unknown, a conservative approach for preserving this (and potentially other) forest-specialist species could be to promote forest restoration projects focused on increasing the number and/or size of forest patches in the landscape (i.e., reverse fragmentation).
Keywords: Callicebus nigrifrons; Forest restoration; Fragmentation debate; Landscape composition; Landscape configuration; Population density